Tectonic and glaciotectonic deformations in the areas of polish lignite deposits = Tektoniczne i glacitektoniczne deformacje na obszarach polskich złóż węgla brunatnego - Widera, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study addresses the complex geology caused mainly by tectonic and glaciotectonic processes in lignite-bearing areas of Poland. Tectonics played a dominant role in the deformation of peat/lignite seams during their deposition. This is especially true for deep grabens where the thickest lignite seams were deposited (e.g., Bełchatów). Conversely, glaciotectonics led to the post-depositional deformation of other deposits (e.g., Sieniawa).
Keywords: lignite; geology deposits; tectonics; glaciotectonics; węgiel brunatny; geologia złóż; tektonika; glacitektonika